A study of investigating the relationship between job satisfaction and turnover intention among preschool teachers in Cheras - Ho, Wai Yin (2024)
As the profession of early childhood teachers is physically and mentally demanding, therefore preschool teachers have a high turnover rate, which highlights the importance of job satisfaction in retaining educators. However, the potential relationship between job satisfaction and turnover intention of preschool teachers is often overlooked in the local context. Therefore, this current study investigated the relationship between total job satisfaction and turnover intention among preschool teachers, with a particular focus on nine subscales of job satisfaction which include pay, promotion, supervision, contingent rewards, fringe benefits, operating procedures, coworkers, nature of work, and communication. This study adopted Maslow's hierarchy of needs theory. A quantitative correlational research design was used to collect data from 80 preschool teachers in Cheras area through the Job Satisfaction Survey (JSS) and the Turnover Intention Scale (TIS-6). The results showed that there was a negative significant correlation between total job satisfaction and turnover intention (r= -0. 635, p<0.001), which means that higher job satisfaction is associated with a lower likelihood of turnover. It was also found that all nine subscales of job satisfaction were significantly correlated with turnover intention, with r values ranging from -.462 to -.937, p<0.001. This study has highlighted to preschool management the importance of improving job satisfaction in reducing the intention rate among preschool teachers. Some recommendations were made to suggest that limitations could be overcome by using physical survey methods, as online fraud issues could affect the effective use of online survey methods.